Impact of Leadership Styles on Employee Performance: An Empirical Study in IT Companies - Radhika Dixit, Manoj Agarwal (European Economic Letters (EEL), 2025)
This study uses qualitative research methodologies to investigate how different leadership styles affect employee performance in IT organisations. Given how quickly the IT industry is developing, strong leadership is essential in determining worker motivation, output, and job happiness. Organisational results, employee motivation, and performance are all significantly influenced by leadership. This qualitative study investigates how employee performance in a few Indian IT organisations is affected by three distinct leadership philosophies: transformational, transactional, and laissez-faire. Five team leaders and twenty workers from mid-sized IT companies participated in semi-structured interviews. Thematic research showed that while transactional leadership increases short-term production through structure and incentives, transformational leadership boosts employee engagement, innovation, and job happiness. On the other hand, unclear leadership frequently results in low morale. The study comes to the conclusion that the most successful leadership style in the fast-paced IT industry is a hybrid one that combines transformational and transactional qualities. There is a discussion of suggestions for staff retention and leadership development.